Vínculo afetivo entre mãe-filho: limites e possibilidades do desenvolvimento da autonomia dos estudantes com deficiência na Educaçâo Superior - Sales, Filipe (2017)
In the family context, the discovery of the deficiency of a child can cause a traumatic experience, altering the family dynamics and consecutively affecting all its members. From the diagnosis, the whole family seeks to reorganize, in order to adapt and regain their balance, because everyone will be affected. Due to this fact, parents, and especially the mother, understand that by having generated this child, has the duty to watch over him, preventing any "evil" from happening, often giving rise to a mother-child dependency, which may jeopardize their development. The present research focused on the development of the autonomy of students with disabilities who are in Higher Education. The objective was to know the process of building and establishing an affective bond between mother and child with disabilities, and its influence for the development of autonomy in the context of Higher Education. The method of qualitative approach was applied to the six participants of the research, that is, 3 mothers and 3 students (children) and used the following instruments of data collection: Two interview scripts on the development of student autonomy, made by the researcher and separately applied to mothers and students (children). The analysis of qualitative data was performed through Content Analysis. It was found that there is a relationship of dependence, but that the relationships established between mother and child with disabilities, did not affect the development of students' autonomy in Higher Education. It was concluded that the principle of the development of autonomy, Is associated to different intervening factors in the process of human development, but did not have a significant impact on people with disabilities.